Integrative analysis of triphenyl phosphate: contextual interpretation of bladder cancer cohort - Zhang, Xiaolei; Huang, Wen; Huang, Tao; Zhang, Jiayi; Xu, Aiming; Cheng, Yidong; Qin, Chao; Lu, Qiang; Wang, Zengjun (Frontiers in Oncology, 2023)
In recent years, organophosphate ester flame retardants (OPFRs) have emerged as preferred alternatives to brominated flame retardants (BFRs) in materials such as building supplies, textiles, and furnishings. Simultaneously, a notable surge in bladder cancer incidences has been observed globally, particularly in developed nations, placing it as the 10th most prevalent cancer type. Among the extensive OPFRs, the linkage between triphenyl phosphate (TPP) and bladder cancer remains inadequately investigated. Hence, our study endeavors to elucidate this potential association. We sourced transcriptome profiles and TPP-related data from The Cancer Genome Atlas and Comparative Toxicogenomics databases. Using the ssGSEA algorithm, we established TPPcorrelated scores within the bladder cancer cohort. Differentially expressed analysis enabled us to identify key genes in bladder cancer patients. We utilized the LASSO regression analysis, along with univariate and multivariate COX regression analyses to construct a prognostic prediction model. To uncover critical pathways involving key genes, we employed GSEA and GSVA enrichment analyses. Molecular docking analysis was performed to determine the binding capability between TPP and proteins. Our findings reveal that the TPP-centric risk model offers valuable prediction for bladder cancer cohorts. Furthermore, the reliability of this TPP-influenced risk model was verified through ROC curve analysis and survival studies. Intriguingly, TPP exposure appears to bolster the proliferation and invasiveness of bladder cancer cells. This study furnishes new insights into the possible benefits of minimizing TPP exposure for hindering bladder cancer progression.